Do Resilience and Social Support Reduce Job Stress? Study on Preschool Teachers - Ega Asnatasia Maharani; Siti Muthia Dinni (Journal of Educational, Health and Community Psychology, 2022)
This study aimed to determine whether resilience and social support could predict job stress on preschool teachers. As many as 120 teachers from Yogyakarta participated in this study. Research instruments were presented through an online platform, comprised of: The Brief Resilience Scale, Multidimensional Scale of Perceived Social Support (MPSS), and The Perceived Stress Scale (PSS-10). Using the SPSS 24.0 for Windows program, the collected data were analyzed using multiple linear regression. The results of the regression analysis showed that resilience and social support significantly predicted job stress on preschool teachers. However, the results of a separate analysis showed that only resilience significantly related to preschool teacher’s stress. This study indicates that teacher’s ability to do internal regulation through stress play a broader role on determining teacher’s job stress level. Furthermore, the prevention program to overcome preschool teacher’s job stress needs to develop by focusing on strengthen this resilience ability.Keywords: Resiliency, Social support, Stress, Teacher